Emotional Intelligence and Perceived Health Related to Expressed Compassion Fatigue: A Study in Health Sector at Regional Level - Ruiz Fernández, María Dolores; Lirola, María-Jesús; Ramos-Pichardo, Juan Diego; Ortíz-Amo, Rocío; Ibáñez-Masero, Olivia; Rodríguez Gómez, Susana; Ortega-Galán, Ángela María (Frontiers in Psychology, 2021)
Background: The work of health professionals often involves physical as well as psychological strain. They constantly deal with traumatic situations of pain and suffering, which destabilize the sense of well-being. Compassion fatigue is a feeling that appears in these cases and is related to other variables such as burnout or emotional drain. Aims: The principal aim of this project was to deepen the analysis of compassion fatigue and how it could be explained through the relationship with other constructs such as emotional intelligence and perceived health. Methods: This work followed the STROBE checklist for cross-sectional studies. In this study 1,521 nurses (Mage = 47.32; SD = 8.44) participated. The responses reported by the nurses were analyzed by classifying them as high or low compassion fatigue and the differences of both groups were analyzed for the variables of emotional intelligence, perceived health and quality of professional life. Results: It was obtained significant differences for all factors except for emotional intelligence factor. A linear regression analysis showed both emotional intelligence and perceived health helped to explain (12%) compassion fatigue. Conclusion: This study provides light on comprehending the conception of compassion fatigue. It highlights the importance of intervention programs that improve the quality of professional life.